Territory and Democratic Politics A Critical Introduction - Mazzoleni, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
Borders, democratic legitimacy, multiscale statehood, governance : the covid crisis has shaken things up and emphasized both the contradictions and the central salience of territories. In this sharp volume Oscar Mazzoleni critically reviews the main debates about territories that have unfold over the last two decades, in particular in geography and political sociology. He makes a powerful insight for a critical territorial approach aiming to analyze democratic politics. Patrick Le Galès, CNRS research professor at Sciences Po, Paris, France Mazzoleni has contributed a brief but encompassing study of the concept of territory in social sciences. This well-written piece analyzes the concept of territory as multidimensional and interdisciplinary. His is a rigorous attempt to offer a systematic framework to make territorial politics part of the contemporary research agenda. In developing a territorial approach, he adds to the field by addressing essential gaps in the literature. Margarita Gomez-Reino Cachafeiro, full professor at the UNED University, Madrid, Spain The book provides a comprehensive and up-to-date introduction to the uses of the concept of territory in the study of democratic politics. The author tests the limits of a literature which avoid territorial dimensions, and reasserts the relevance of the concepts of territory and territorial space in the understanding of contemporary politics. With a political sociological perspective, but engaging in an interdisciplinary dialogue, the book draws a new conceptual framework focusing on both traditional and innovative topics: state-building and the transformation of nation-states, the changes in democratic citizenship, the relevance of territory for voting behaviour, the territorial dimensions of populism and the experience of the pandemic, taken as a global territorial crisis. Oscar Mazzoleni is Directorof the Research Observatory for Regional politics at the University of Lausanne, Switzerland.
Chapter 1: Why and how territory -- Chapter 2: Strength and limits of unterritorial approaches -- Chapter 3: Towards a territory-oriented approach -- Chapter 4: Beyond the territorial state? -- Chapter 5: Changing democratic citizenship -- Chapter 6: Territorial voting -- Chapter 7: Territorial populism -- Chapter 8: A global territorial crisis -- Chapter 9: Thinking democratic politics with territory.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Europe -- Politics and government; Political sociology; Human geography; Cultural geography; European Politics; Political Sociology; Social and Cultural Geography